Providing Value-Based Service to a Sprawling Orthopaedics Practice - Zoga, Adam C.; Rozenberg, Aleksandr; Vaccaro, Alexander R.; Tomlinson, Christopher C. (Seminars in Musculoskeletal Radiology, 2018)
Health care in the United States is changing, and diagnostic radiology is attempting to adapt to the new norm. A view of the landscape shows mergers, acquisitions, and radiology practices becoming larger. Musculoskeletal (MSK) radiology is trending toward subspecialization, and orthopaedic surgery practices are demanding quality, convenience, and efficiency in imaging services. In other industries, optimization of operations and strategic deployment of resources are standard, but radiology is not quite there yet. This article details our opportunities in MSK imaging to increase market share through service, added value, and improved operational efficiency.
Keywords: musculoskeletal; orthopaedics; value; subspecialty reads